Early Shift of Attention Is Not Regulated by Mind Wandering in Visual Search - Vogelgesang, Lena; Reichert, Christoph; Hinrichs, Hermann; Heinze, Hans-Jochen; Dürschmid, Stefan (Frontiers in Neuroscience, 2020)
Unique to humans is the ability to report subjective awareness of a broad repertoire of external and internal events. Even when asked to focus on external information human´s mind repeatedly wanders to task unrelated thoughts limiting reading comprehension or the ability to withhold automated manual responses flowing into the attentional decoupling account of mind wandering (MW). However, manual responses are not an ideal parameter to study attentional decoupling given that during MW the online adjustment of manual motor responses is impaired. Critically examined, whether early attentional mechanisms are indeed down-regulated during MW or only motor responses being slowed to prevent from overhasty decisions is not clear. In contrast to manual motor responses eye movements are considered a sensitive proxy of attentional shifts. Using a simple target detection task, we asked subjects to indicate whether a target was presented within a visual search display by pressing a button while we recorded eye movements and in an unpredictable order asked the subjects to rate their actual level of MW. Generally, manual reaction times increased with MW and were longer in target absent trials, but this reaction time increment did not differ with the mental state. Hence, even in trials with MW subjects detected earlier a presented than an absent target. The decoupling account would predict more fixations of the target before pressing the button during MW. However, our results did not corroborate this assumption. Most importantly subject´s time to direct gaze at the target was equally fast in trials with and without MW. Our results corroborate our hypothesis that during MW early attentional processes are not decoupled but selectively manual motor responses are slowed.